EFFECT OF WORK TRAINING, COMPENSATION, AND WORK EXPERIENCE ON WORK ACHIEVEMENT (CASE STUDY: EMPLOYEES OF PT. KONVERGENSI MITRA SOLUSI YOGYAKARTA) - Prayekti, Prayekti; Fau, Nefral Yusuf; Kirana, Kusuma Candra (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study is aimed at knowing the effect of job training, compensation, and work experience on employee performance. The population taken in this study is 88 employees of PT. Konvergensi Mitra Solusi Yogyakarta. In the samples taken non-sampling is conducted by a sampling used as an inducive sampling. Data was collected using a prepared questionnaire using multiple linear regression analysis. Research results on employment training variables and work experience suggest that there is a significant impact on employee performance. While research on the compensation variables suggests that there is no significant impact on employee performance.